Identification of an erm(A) Erythromycin Resistance Methylase Gene in Streptococcus pneumoniae Isolated in Greece - Syrogiannopoulos, George A. (American Society for Microbiology, 2001)
In a serotype 11A clone of erythromycin-resistant pneumococci isolated from young Greek carriers, we identified the nucleotide sequence of erm(A), a methylase gene previously described as erm(TR) in Streptococcus pyogenes. The erm(A) pneumococci were resistant to 14- and 15-member macrolides, inducibly resistant to clindamycin, and susceptible to streptogramin B. To our knowledge, this is the first identification of resistance to erythromycin in S. pneumoniae attributed solely to the carriage of the erm(A) gene.